1989
DOI: 10.1002/bem.2250100203
|View full text |Cite
|
Sign up to set email alerts
|

Search for cyclotron resonance in cells in vitro

Abstract: There are a number of reports of the plasma membrane transport of Ca2+ in biological systems being enhanced by low frequency electromagnetic fields (EMF), including reports that the enhancement involves a resonance-type response at the cyclotron frequency for Ca2+ ions for geomagnetic values of the magnetic field. Using the fluorescent probe fura2, we find no evidence for changes in cytosolic calcium concentration in BALB/c3T3, L929, V-79, and ROS, a rat osteosarcoma cell line, at the application of both reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Over the past two decades, research using diverse in vitro models has demonstrated the ability of MF exposure to modify calcium metabolism, presumably by affecting calcium flux across membranes (4)(5)(6)(7)(8)(9)(10). However, several investigations have not detected an effect of MF on calcium metabolism or flux in a variety of cell types (11)(12)(13)(14)(15). This (24) reported that calcium uptake in rat lymphocytes was increased by brief exposures to 60-Hz MF only in cells stimulated with the mitogen concanavalin A (ConA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, research using diverse in vitro models has demonstrated the ability of MF exposure to modify calcium metabolism, presumably by affecting calcium flux across membranes (4)(5)(6)(7)(8)(9)(10). However, several investigations have not detected an effect of MF on calcium metabolism or flux in a variety of cell types (11)(12)(13)(14)(15). This (24) reported that calcium uptake in rat lymphocytes was increased by brief exposures to 60-Hz MF only in cells stimulated with the mitogen concanavalin A (ConA).…”
mentioning
confidence: 99%
“…We conducted our studies with both 20x and 40x objectives, whereas Lindstrom et al (25,26) used a IOOx objective. Too few cells were contained within the field of view at 100x (approximately [8][9][10][11][12] for the use of the statistical approach in the present study. On the other hand, a 100x objective provides superior assessment of morphology and therefore was the most useful method for the approach taken by Lindstrom et al (25).…”
mentioning
confidence: 99%
“…The immediate mode of action of magnetic fields, and the reason for their frequency dependence, may relate to "cyclotron resonance" causing altered transport of calcium ions through channels into the cells [Blackman et al 1988[Blackman et al , 1989Liboff and McLeod 19881, although not all work supports this [Parkinson and Hanks 1989]. Despite these other changes in DNA synthesis, there is no increase in single-strand DNA breaks in Chinese Hamster Ovary cells exposed to 60…”
mentioning
confidence: 68%
“…Obviously, there is a need to refine the theoretical description of this phenomenon before it can form a plausible basis for weak field interactions with biological membranes. Also, two recent studies have failed to observe an effect of combined fields on Na + and Ca ++ transport under ion cyclotron resonance conditions (48, 69). A recent theoretical model has been proposed in which the resonant effects of combined static and ELF fields are visualized as resulting from an effect on the vibrational energy levels of an ion, with a resulting effect on its interaction with ligand binding sites (45).…”
mentioning
confidence: 98%